Migración de peruanos a Japón - Aquino Rodríguez, Carlos (2010)
The article describes the situation of Peruvians migrants in Japan. Their number decreased in 2009 because the Japanese economy experimented a recession. First the reasons behind the departure of Peruvian to Japan are addressed, second why some of them came back to Peru is seen, and third the amount of remittances from that country is analyzed, and lastly some conclusions are given.